2018
DOI: 10.2196/10157
|View full text |Cite
|
Sign up to set email alerts
|

A Smartphone App to Foster Power in the Everyday Management of Living With Schizophrenia: Qualitative Analysis of Young Adults’ Perspectives

Abstract: BackgroundLiterature indicates that using smartphone technology is a feasible way of empowering young adults recently diagnosed with schizophrenia to manage everyday living with their illness. The perspective of young adults on this matter, however, is unexplored.ObjectiveThis study aimed at exploring how young adults recently diagnosed with schizophrenia used and perceived a smartphone app (MindFrame) as a tool to foster power in the everyday management of living with their illness.MethodsUsing participatory … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
37
1
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(41 citation statements)
references
References 57 publications
0
37
1
3
Order By: Relevance
“…Participants reported that the perceived changes they experienced in their mental health as a result of using an intervention affected their further engagement. Perceived symptom improvement facilitated further engagement [ 89 , 95 , 103 , 145 , 146 , 189 , 197 - 199 ], whereas exacerbation of symptoms negatively impacted engagement [ 49 , 93 , 104 , 200 ]. Other negative impacts of the intervention were also observed as barriers to ongoing user engagement.…”
Section: Resultsmentioning
confidence: 99%
“…Participants reported that the perceived changes they experienced in their mental health as a result of using an intervention affected their further engagement. Perceived symptom improvement facilitated further engagement [ 89 , 95 , 103 , 145 , 146 , 189 , 197 - 199 ], whereas exacerbation of symptoms negatively impacted engagement [ 49 , 93 , 104 , 200 ]. Other negative impacts of the intervention were also observed as barriers to ongoing user engagement.…”
Section: Resultsmentioning
confidence: 99%
“…Less is known about efficacy of these interventions: whereas technologies target different symptoms, they are evaluated with different assessment tools. There are studies, that report results on feasibility of digital intervention and users’ satisfaction (Dennison et al, 2013; Terp et al, 2018; Wartena & van Dijk, 2013), which requires further investigations of clinical efficacy. Representativity of clinical effects in another studies is a challenge due to a low number of participants (only six technologies were tested on more than 100 participants; Bain et al, 2017; Berrouiguet et al, 2017; Španiel et al, 2012), lack comparisons with control group or ‘digital placebo’ effect (Torous & Firth, 2016) and unknown efficacy of long-term follow-up.…”
Section: Resultsmentioning
confidence: 99%
“…This included reminding the participant of an inbuilt five-hour window to respond to questions, a feature which was included as a result of beta-testing feedback that suggested some people felt pressured by a limited response window. A heightened sense of paranoia and increased fear of recurrence were included in our protocol and medical device registration documents as anticipated risks of the intervention and heightened feelings of paranoia as a result of routine monitoring in psychosis have been reported elsewhere (Eisner et al, 2019;Terp, Jørgensen, Laursen, Mainz, & Bjørnes, 2018).…”
Section: Empower (Early Signs Monitoring To Prevent Relapse In Psychomentioning
confidence: 99%